Analysis of ground settlement in land reclamation projects - Syed Hanan Haney Al-Husaini (2017)
Land reclamation projects pose great efforts and a lot of difficulties needed to overcome before its completion. The different soil layers and types are challenges faced as different types of soil have different characteristics. Such characteristics are the coefficients of consolidation, water content, effective stresses etc. The soil type usually present below seabed is the marine clay, which is a very weak clay compared to normal soil. Thus, this usually makes land reclamation more time consuming and difficult to carry out.